SILCC - VII. Gas kinematics and multiphase outflows of the simulated ISM at high gas surface densities - Rathjen, Tim-Eric; Naab, Thorsten; Walch, Stefanie; Seifried, Daniel; Girichidis, Philipp; Wünsch, Richard (Monthly notices of the Royal Astronomical Society, 2023)
We present magnetohydrodynamic (MHD) simulations of the star-forming multiphase interstellar medium (ISM) in stratified galactic patches with gas surface densities Σgas = 10, 30, 50, and 100 M⊙pc−2⁠. The silcc project simulation framework accounts for non-equilibrium thermal and chemical processes in the warm and cold ISM. The sink-based star formation and feedback model includes stellar winds, hydrogen-ionizing UV radiation, core-collapse supernovae, and cosmic ray (CR) injection and diffusion. The simulations follow the observed relation between Σgas and the star formation rate surface density ΣSFR. CRs qualitatively change the outflow phase structure. Without CRs, the outflows transition from a two-phase (warm and hot at 1 kpc) to a single-phase (hot at 2 kpc) structure. With CRs, the outflow always has three phases (cold, warm, and hot), dominated in mass by the warm phase. The impact of CRs on mass loading decreases for higher Σgas and the mass loading factors of the CR-supported outflows are of order unity independent of ΣSFR. Similar to observations, vertical velocity dispersions of the warm ionized medium (WIM) and the cold neutral medium (CNM) correlate with the star formation rate as σz∝ΣaSFR⁠, with a ∼ 0.20. In the absence of stellar feedback, we find no correlation. The velocity dispersion of the WIM is a factor ∼2.2 higher than that of the CNM, in agreement with local observations. For ΣSFR≳1.5×10−2M⊙yr−1kpc−2 the WIM motions become supersonic.
Veröffentlicht: 14. April 2023
Gesehen am 24.07.2023